Evaluation of biogenic amines and microbial composition in the Chinese traditional fermented food grasshopper sub shrimp paste. (December 2020) - Sang, Xue; Ma, Xinxiu; Hao, Hongshun; Bi, Jingran; Zhang, Gongliang; Hou, Hongman
Abstract: The presence of biogenic amines (BAs) in fermented foods represents a health risk for consumers. Therefore, understanding how BAs are accumulated would enable better control of their content in fermented foods. In this study, the BA profiles of grasshopper sub shrimp pastes produced in different typical regions (Panjin, Rongcheng, Shouguang, Dalian, Tangshan, Qinhuangdao and Yantai) around the Bohai Sea were evaluated. Among the microbial diversity found in the shrimp pastes, Tetragenococcus, Lactobacillus, Aspergillus and unclassified_k_Fungi were the predominant genera. The results of RDA correlations between physicochemical-microbial indexes and BAs suggested that the high BAs content in shrimp paste might be linked to the salinity of products and halophilic bacteria present in shrimp paste. A total of 442 strains of halophilic bacteria were identified and the five most abundant genera were Bacillus, Staphylococcus, Tetragenococcus, Virgibacillus and Oceanobacillus . Among these, 95.10% of species could produce BAs although their production appeared to vary greatly, with 30 strains considered as high producers, achieving a BA concentration of 787.54 ± 20.87 mg/kg. Thus, controlling these bacteria might be the key to controlling the BA content in the shrimp paste. Highlights: Complete profile of microbiota was evaluated and that had regional differences. Types and contents of BAs varied among samples of seven typical regions in China. Halophilic bacteria and salinity of samples may be main factors for high BA contents. Salinity of the products at 20–25% would keep the BA contents within the safe limit. 30 high-BA producing strains might be responsible for the accumulation of BAs.